Systematic Literatur Review: Analisis Struktur Persajakan Pada Puisi “Bahasa, Bangsa” Karya Mohammad Yamin - Shafira Putri Cantika; Usiono Usiono (PT. Alahyan Publisher Sukabumi, 2025)
The purpose of this study is to (1) analyze the poetical structure found in Muhammad Yamin's poem Language, Bangsa. (2) interpretation of the content from the perspective of the reader. This study's methodology is a qualitative descriptive approach. Reading, reading, and recording strategies are the methods utilized to acquire the data. The verses of Muhammad Yamin's poem Bahasa, Bangsa serve as the source of the research's data. Methods of data analysis employed It is a content analysis technique used in this investigation. The study's findings demonstrate that: (1) Each poem's inherent structure takes the form of rhymes or classic poetry. Considering the sentence structure (2) the interpretation analysis.